Pengaruh Servant Leadership terhadap Perceived Organizational Support, Job Embeddedness, Job Satisfaction, dan Turnover Intentions pada Bank Swasta di Jakarta Barat - Resga, Arie; Nurhasanah, Nina (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
This study aims to examine the influence of servant leadership (SL) on perceived organizational support (POS), job satisfaction (JS), job embeddedness (JE), and turnover intentions (TI) among private bank employees in West Jakarta. The research is motivated by the high turnover rate in the banking industry, despite organizational efforts to strengthen leadership and employee support. A total of 154 employees participated by completing an online Likert-scale questionnaire, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.1.0.9. The findings reveal that SL positively and significantly influences POS (β=0.667), JS (β=0.585), and JE (β=0.579). Furthermore, POS (β=−0.328), JE (β=−0.386), and JS (β=−0.220) significantly and negatively affect TI. Predictive relevance is supported with Q² values ranging from 0.283 to 0.604, while model fit testing using SRMR yielded 0.050 (saturated) and 0.127 (estimated). Bootstrapping was conducted with 5,000 resamples, two-tailed testing, bias-corrected accelerated (BCa), and 95% confidence intervals. Theoretically, this research strengthens the literature by demonstrating that SL enhances workplace relationships through improved POS, JS, and JE, which subsequently reduces turnover intentions. Practically, the findings provide implications for banking management to adopt servant leadership as a strategic approach to employee retention. Nevertheless, despite high levels of POS, JS, and JE, some respondents still report turnover intentions, indicating the presence of unmodeled external factors such as career opportunities, workload, or industry dynamics. This study is limited by its cross-sectional design and one-time self-report measurement; thus, generalizations and causal inferences should be made with caution.